Agreements/disagreements about the inclusive process in Higher Education: an exploratory study - Lígia da Silva Marques; Cláudia Gomes (Universidade Federal de Santa Maria (UFSM), 2014)
With the intention to characterize the teachers agreement about the inclusion of students with deficiencies, global disorders development and giftedness in college; as well as the evaluation that the teachers themselves do as the professional and institutional capacity necessary to this process; this study investigated 20 teachers in a federal university of Minas Gerais, they answered a questionnaire about the investigate thematic. After data quantitative analysis, the following results were obtained: the teachers were aware of the necessity to establish an effective inclusive scene in the institution and confirmed the necessity of physical and employees' preparation to do it; therefore, they didn't feel capable enough to do it. In relation to the concordance of the inclusion of people with sensory deficiencies, it was evident that teachers reflect total or partial agreement; now in case of necessities linked with behaviors disorders, intellectual deficit or multiples deficiency, they disagree. This seems to denote that higher the necessity of commitments and differentiated professional actions, such as pedagogical and curriculum adaptations; less is the agreement with the inclusion, mostly for the teachers who teach in exact science area. As final consideration, we emphasize the necessity to move forward for discussion and educational practices which support the inclusive professional action, considered by the teachers their competence and responsibility; understanding this, which provides the introduction and the fortification of actions that ensure attitudinal, pedagogical and institutional conditions could support the construction a university wirh the intention of providing access, permanence and development to all the students.